Dynamic Contrast Enhanced MRI of the Prostate: Comparison of Gadobutrol and Gd-DTPA - Durmus, T.; Vollnberg, B.; Schwenke, C.; Kilic, E.; Huppertz, A.; Taupitz, M.; Franiel, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To evaluate the enhancement profile of the macrocyclic contrast medium (CM) gadobutrol in comparison to linear CM Gd-DTPA in DCE-MRI of the prostate.Materials and Methods: In total 53 patients with prostata cancer (PCa) were included, who received a radical prostatectomy after multiparametric MRI of the prostate including DCE-MRI. Using circular regions of interests normal peripheral zone (PZ) and PCa foci > 5 mm in diameter (42 and 34 foci in Gd-DTPA and gadobutrol group, respectively) were analysed in DCE-MRI. Enhancement curves (Type I, II and III) and pharmacokinetic parameters were analyzed qualitatively and quantitatively and compared using mixed linear models (two sided p-values < 0.05 were regarded significant).Results: There was no significant difference in frequencies of curve types I, II or III in the normal PZ (p = 0.63) or in PCa foci (p = 0.75). PCa with a Gleason score ≥ 7 had in comparison to Gleason ≤ 6 significantly more often a Wash-Out-curve (Type III) with both CM (p = 0.02). The relative peak enhancement was in the PZ (Gd-DTPA 1.4 a. u. [1.20; 1.59], gadobutrol 1.58 a. u. [1.37; 1.78]) and in PCa foci (Gd-DTPA 1.56 a. u. [1.41; 1.71], gadobutrol 1.76 a. u. [1.59; 1.94]) significantly higher with gadobutrol (p = 0.04). The pharmacokinetic parameters Ktrans und kep were higher in PCa foci than in PZ (p < 0.0001 and p = 0.002, respectively) without significant difference of the parameter values between both CM (p = 0.65).Conlusion: This study is the first systematic comparison of gadobutrol and Gd-DTPA in DCE-MRI of the prostate. The relative peak enhancement is higher using gadobutrol compared to Gd-DTPA in DCE-MRI. There was no statistically significant difference in curve types or the pharmacokinetic parameters in PCa or normal PZ between both CM.Key Points:Citation Format:
Keywords: prostate; MR-imaging; contrast agents; gadolinium; neoplasms